Kesadaran hukum dalam pencegahan tindak kekerasan seksual dan penyalahgunaan narkotika di Desa Reksosari Kabupaten Semarang - Farida Yuli Astuti; Surya Latifatul Nihayati; Iin Afriyanti; Dhiya Adila Nasywa Iskandar; Dwi Ardhi Ana Sal Sabilla; Silvania Aulia Fitri; Muhammad Hafid Ludfia Musthofani Amin; Muhammad Syamsul Arifin; Arief Ardiansyah (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
Sexual violence and narcotics abuse remain serious problems in Indonesia, including in rural areas. Low public legal awareness is often a factor contributing to ineffective prevention efforts. This activity aims to improve the legal understanding and awareness of the community in Bawangan Hamlet, Reksosari Village, Suruh District, Semarang Regency, in preventing sexual violence and narcotics abuse. The method used was Participatory Action Research (PAR), involving the community actively through socialization, interactive discussions, and legal awareness training. The activity was conducted in August 2025. The socialization focused on providing insight into relevant regulations, while the training emphasized community skills in identifying, preventing, and following up on issues within their environment. This activity provided benefits such as increased legal understanding, the development of social concern, and the growth of collective awareness regarding the importance of prevention. However, the PAR approach has limitations, particularly in unifying community perceptions of key issues and in determining the most effective resolution strategies.